Fabric Based Wearable Biosensor for Continuous Monitoring of Steroids. (7th July 2017) - Manickam, Pandiaraj; Madhu, Sekar; Fernandez, Renny Edwin; Viswanathan, C; Bhansali, Shekhar
Abstract : This paper describes the construction of a biochemical sensor platform on thread for continuous monitoring of cortisol levels. Metal complex porphyrin conjugated metal oxide nanoparticle was used as a catalyst for the electrochemical conversion of cortisol. Scanning electron microscopy and energy dispersive X-ray analysis (EDX) was used to characterize the sensor architecture. Voltammteric measurement were performed in PBS at pH 7.0 to detect cortisol in the range of 50 pM to 350 nM with a detection limit of 10 pM. The thread based sensor can be integrated with fabrics on a wearable platform to continuously monitor cortisol levels in sweat.